Galectin-3 and Estrogen Receptor Alpha as Prognostic Markers in Prolactinoma: Preliminary Results From a Pilot Study - Bima, Chiara; Chiloiro, Sabrina; Giampietro, Antonella; Gessi, Marco; Mattogno, Pier Paolo; Lauretti, Liverana; Anile, Carmelo; Rindi, Guido; Pontecorvi, Alfredo; De Marinis, Laura; Bianchi, Antonio (Frontiers in Endocrinology, 2021)
Introduction: Prolactin-secreting pituitary tumors (PRL-omas) are in most of cases benign neoplasia. However, a not-negligible percentage of cases shows an aggressive behavior. Prognostic markers may allow the identification of aggressive cases. In this study, we investigated the prognostic role of galectin-3 and of the estrogen receptor alpha (ERα), recently suggested as predictive of aggressiveness and poor prognosis. Patients and methods: A mono-centric and retrospective study was conducted on consecutive cases of PRL-omas, underwent first line treatment with surgery and followed-up for at least five years. The immunohistochemical expression of ERα and galectin-3 was investigated in each case. Results: 36 patients were enrolled. Galectin-3 resulted positive in 11 patients (30.6%). The median expression of ERα was 85% (IQR: 37). Among the group of 21 patients underwent radical surgery (58.3%), recurrence occurred in 12 cases (33.3%). 27 patients were treated post-surgery with dopamine agonist (DA) (12 for recurrence and 22 for history of partial surgery). 13 patients (48.1%) were responsive to DA. Six of 11 cases positive for galactin-3 underwent partial surgery (54.5%, p<0.001). Recurrence occurred in all the five cases underwent radical surgery and positive for galectin-3 (p=0.03). Galectin-3 resulted positive in 9 patients resistant to DA treatment (81.1%, p=0.01). ERα expression resulted lower in tumors positive for galectin-3 (p<0.001), with mitotic activity (p=0.012), with higher Ki67 Li (p<0.001) and in males with post-surgical recurrence (p<0.001). Conclusion: Galectin-3 and ERplay as markers of aggressiveness and prognosis in PRL-omas and may be tested for identify the aggressive forms of disease.